Transporter Protein-Guided Genome Mining for Head-to-Tail Cyclized Bacteriocins - Daniel Major; Lara Flanzbaum; Leah Lussier; Carly Davies; Kristian Mark P. Caldo; Jeella Z. Acedo (Molecules, 2021)
Head-to-tail cyclized bacteriocins are ribosomally synthesized antimicrobial peptides that are defined by peptide backbone cyclization involving the N- and C- terminal amino acids. Their cyclic nature and overall three-dimensional fold confer superior stability against extreme pH and temperature conditions, and protease degradation. Most of the characterized head-to-tail cyclized bacteriocins were discovered through a traditional approach that involved the screening of bacterial isolates for antimicrobial activity and subsequent isolation and characterization of the active molecule. In this study, we performed genome mining using transporter protein sequences associated with experimentally validated head-to-tail cyclized bacteriocins as driver sequences to search for novel bacteriocins. Biosynthetic gene cluster analysis was then performed to select the high probability functional gene clusters. A total of 387 producer strains that encode putative head-to-tail cyclized bacteriocins were identified. Sequence and phylogenetic analyses revealed that this class of bacteriocins is more diverse than previously thought. Furthermore, our genome mining strategy captured hits that were not identified in precursor-based bioprospecting, showcasing the utility of this approach to expanding the repertoire of head-to-tail cyclized bacteriocins. This work sets the stage for future isolation of novel head-to-tail cyclized bacteriocins to serve as possible alternatives to traditional antibiotics and potentially help address the increasing threat posed by resistant pathogens.